Vulnerabilidade de agricultores familiares da cadeia de produção de biodiesel de dendê à extremos de precipitação na comunidade Águas Pretas, Moju (PA) - BARRETO, Adriana Gisely Tavares (Universidade Federal do Pará, 2013)
The climate extremes have a negative impact in the Brazilian agribusiness and threaten the development of the rural communities that are mainly of the natural resources. That’s why it’s necessary to study the productive chain of oil palm (Elais guineensis Jacq.) based on future climatic risks, because the state of Pará is the largest domestical producer of oil plam and the structured chain with the integration of the family agriculture to the agricultural chain. The objective of this research was to analyze the vulnerabilities of family farmers of the “Aguas Pretas” community in the city of Moju, state of Pará, inserted in the production chain of biodiesel of oil palm, facing the precipitation extremes. The research was made in two steps: the first analyzed the climatic extremes of the precipitation series from 1981 to 2009 applying the descriptive method and the quantis, and the second step analyzed the vulnerability of the farmers through the variable/indicators of socioeconomic disadvantage, technological and of perception, that represented a vulnerable situation. To identify farmers’ vulnerability, the factorial analyses for main components was used, the index elaboration of climatic vulnerability and the group analyses, where 22 farmers were placed in five categories of predefined classification. The results have shown that the occurrence of very dry extremes and very rainy in the data series in the years of 1981 to 2009 in the city of Moju (PA). The identified climatic risk in the city represents a great threat to oil palm production, because the extreme impacts of precipitation over the plant are not only development stages but also the partial and total reduction of oil palm bunches. Those impacts in long term, directly affects the family farmers that are dependants of the exclusive selling of palm oil bunches to the industry, as well as it compromises the inclusion objectives of social inclusion and renewable energy production of the biodiesel Program. The family farmers from “Águas Pretas” community in the production chain of palm oil biodiesel reacted in different ways, considering the socioeconomic factors, technological and of perception factors, being distributed in five different categories of vulnerability (high, middle high, middle low and low). The groups of vulnerability of higher interest in the research were of high and low vulnerability, corresponding to 14% (3 farmers) and 18% (farmers), respectively, of the total interviewed farmers. The group of high vulnerability was characterized by farmers that used with low efficiency the highest part of the variables of disadvantages, indicating difficulties to compete and adapt, in case of climate extremes. The group of low vulnerability was characterized by farmers that uses with efficiency all the macro variables studied, showing socioeconomics advantages, technological and of perception. This group appeared to be more adapted in case of climate extremes, in the biodiesel chain, with the possibility to be a parameter to strategies elaboration of local adaptation. The risk perception and the raised factors have appeared to be a strong resource to analyze the vulnerability situation of local farmers. The farmer perception is oriented based on his convictions and daily experiences, being of great importance to the adaptable strategies elaboration to face climate extremes.